Music-Makers and Reformed Theology - Jahdiel N Perez (Societas Dei: Jurnal Agama dan Masyarakat, 2016)
ABSTRACT: If Reformed theology hopes to impact contemporary and future societies as much as possible it will have to harness the unique power of music to influence the world beyond the walls of the Church. In this essay, I want to draw attention to the ways in which Christianity, in general, and Reformed theology, in particular, are criticized through music and what we can do to respond. I will introduce an approach to Christian apologetics, which I call sonic-apologetics that enables our music-makers to defend the faith musically. In the first part of this paper, I will discuss five problems to which sonic-apologetics is an answer. This will anchor the second part of this essay, in which I construct sonic-apologetics from three notions: (1) methodological emphasis on effects, (2) genres of expression, and (3) the distinction between linear and angled apologetic responses. In the final part of this essay, I present two different study cases of sonic-apologetics. Nothing about what I will discuss regarding sonic-apologetics changing existing liturgical norms of Christian churches, especially Reformed ones. It does, however, call for those producing and performing music in these churches to direct their music-making interests and abilities toward the world outside the church walls. KEYWORDS: reformed theology, music, sonic-apologetics.